Interstitial tuning of Y3+ sites with Li+ sensitized improved Tb3+emission for WLED application - Davidson Pyngrope; Phlegon Syndai; Amresh I Prasad (Next Nanotechnology)
A series of wide-ranging single phase YPO4:xTb3+ phosphor was prepared by wet chemical route. In order to maximise the use of YPO4:Tb3+ nanoparticles in WLED, this work used Li+ sensitization to interstitially modify the particles' photoluminescence intensity. The prepared nanoparticles are characterized using X-Ray diffraction, FT-IR, TEM and Photoluminescence. The annealing effect on the particle size, morphology and its luminescence intensities are studied. This increased crystallinity led to a rise in the photoluminescence intensity of the nanoparticles. YPO4:Tb3+ nanoparticles' excitation and emission spectra were shown by photoluminescence investigations. Optical absorption and emission spectra confirmed all peaks associated to various transitions of the Tb3+ ions. Because of the increased crystallinity and decreased water content, the emission intensity rose with the annealing temperature. Li+ co-doping increased the emission intensity even more; where the emission intensity showed seven times. The results emphasise the significance of Li+ sensitization and annealing temperature in adjusting the luminous properties for possible uses in WLED and other display systems